Atrio-Ventricular Septal Defect in Pregnant Women, How to Deal with It : A Case Study - Devie Caroline; Moh. Yogiarto (ACI (Acta Cardiologia Indonesiana), 2017)
Pregnancy is not always well tolerated in women with congenital heart disease (CHD) such as atrio-ventricular septal defect (AVSD), predominantly due to heart failure deterioration and increasing pulmonary hypertension (PH). Managements of those patients are challenging, especially during third trimester and after delivery care. Decision about time of termination, mode of delivery and anesthetic management are also debatable. In this article we report two similarcases of pregnant women with AVSD and severe PH. The frst patient was 27 years old, 28-29 weeks pregnant came with shortness of breath. She had history of miscarriage once. Based on her transthoracal echocardiography, she was diagnosed with AVSD partial type (primum ASD) with severe PH and then treated with intravenous furosemide, oral beraprost and oral sildenafl. The second patient was 27 years old 30-31 weeks pregnant with shortness of breathand appeared cyanotic. She delivered her frst child spontaneously without any symptoms. Based on her transthoracal echocardiography she was diagnosed with AVSD transitional type (large primum ASD with small inlet VSD) and Eisenmenger syndrome. She was treated with intravenous furosemide and oral beraprost. Those two patients underwent planned C-section under general anesthesia, both babies were survived but the patient did not survived severaldays after the procedure due to PH crisis. Until now, management PH associated with CHD in pregnant women is complex. Fluid management and pulmonary artery hypertension (PAH)- targeted therapies are important. Mode of delivery on this cases is also remain debated. Some studies stated planned C-section might be a better choice and combination epidural and lowdose spinal anesthesia might be better than general anesthesia. At the end, when a woman with CHD and PH chooses to continue pregnancy, multidisciplinary team approach is crucial to achieve good outcomes.